Systematic review and Meta-Analysis of Mendelian randomisation analyses of Abdominal aortic aneurysms. (August 2021) - Ibrahim, Muhammad; Thanigaimani, Shivshankar; Singh, Tejas P; Morris, Dylan; Golledge, Jonathan
Abstract: Introduction: Mendelian randomisation (MR) has been suggested to be able to overcome biases of observational studies, but no meta-analysis is available on MR studies on abdominal aortic aneurysm (AAA). This systematic review and Meta-analysis examined the evidence of causal risk factors for AAA identified in MR studies. Methods: Publicly available databases were systematically searched for MR studies that reported any causal risk factors for AAA diagnosis. Meta-analyses were performed using random effect models and reported as odds ratio (OR) and 95% confidence intervals (CI). Study quality was assessed using a modified version of Strengthening the Reporting of Mendelian Randomisation Studies (STROBE-MR) guidelines. Results: Sixteen MR studies involving 34, 050 patients with AAA and 2, 205, 894 controls were included. Meta-analyses suggested that one standard deviation increase in high density lipoprotein (HDL) significantly reduced (OR: 0.66, 95% CI: 0.61, 0.72) and one standard deviation increase in low density lipoprotein (LDL) significantly increased the risk (OR: 1.68, 95%, CI: 1.55, 1.82) of AAA. One standard deviation increase in triglycerides did not significantly increase the risk of AAA (OR: 1.21, 95% CI: 0.86, 1.71). Quality assessment suggested that ten and five studies were of low and moderate risk of bias respectively, with one study considered as high risk of bias. Conclusion: This meta-analysis suggests LDL and HDL are positive and negative casual risk factors for AAA.